DISTRIBUSI SKOR KALSIUM ARTERI KORONER BERDASARKAN USIA DAN JENIS KELAMIN PADA POPULASI SEHAT - Andreas Hartanto Santoso; Caesar Rio Julyanto Putra; Josephine Rasidi; Hoo Felicia Davina Hadi Gunawan; Joshua Henrina Sundjaja; Irvan Cahyadi; Leonardo Paskah Suciadi (Bahasa Indonesia, 2021)
Introduction: Coronary Artery Calcification (CAC) score may give information in cardiovascular risk stratification asymptomatic individuals. Profiles and distribution of CAC scores are still scarce in Indonesia. This study aimed to evaluate the distribution of CAC based on age and gender in asymptomatic patients. Methods: Subjects were asymptomatic Asian above 40 years-old undergoing cardiovascular check-up, including Computed Tomography (CT) CAC at Siloam Heart Institute, from April 2018 to August 2019. Data were obtained retrospectively and analyzed statistically with IBM SPSS version 22. Results: A total of 1640 patients were enrolled, with males slightly more than half. The mean age was 55,6 ± 9,6 years, with age group of 50-59 years as the majority (35,9%). Almost half of the subjects had zero CAC score. Around two-thirds of females, particularly below 50 years old, had zero CAC scores. CAC scores >400 were more prevalent in males across all age groups. The majority of healthy males had a CAC score between 0-99. There was a positive correlation between age and CAC scores in both genders. Females with CAC score >400 were found mostly after 70 years old, ten years older than males. CAC score >1000 was more prevalent in older males compared to females. Conclusion: The distribution of CAC score is remarkably affected by age and gender. Zero CAC score is found predominant in our subjects. CAC scores of ≥400 are common in males across all age groups. CAC score >1000 is more exclusively found in the elderly male